2019
DOI: 10.1016/j.jalgebra.2019.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Abstract homomorphisms from locally compact groups to discrete groups

Abstract: We show that every abstract homomorphism ϕ from a locally compact group L to a graph product G Γ , endowed with the discrete topology, is either continuous or ϕ(L) lies in a 'small' parabolic subgroup. In particular, every locally compact group topology on a graph product whose graph is not 'small' is discrete. This extends earlier work by Morris-Nickolas.We also show the following. If L is a locally compact group and if G is a discrete group which contains no infinite torsion group and no infinitely generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…We want to do this with geometric means. This is inspired by [KV19]. Given a graph product G Γ , there exists a finite dimensional right-angled building X Γ on which G Γ acts isometrically [Dav98, Theorem 5.1], see also [KV19, Section 3.5].…”
Section: The Class G and Graph Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…We want to do this with geometric means. This is inspired by [KV19]. Given a graph product G Γ , there exists a finite dimensional right-angled building X Γ on which G Γ acts isometrically [Dav98, Theorem 5.1], see also [KV19, Section 3.5].…”
Section: The Class G and Graph Productsmentioning
confidence: 99%
“…Given a finite simplicial graph Γ = (V, E) and a collection of groups G = {G u | u ∈ V }, the graph product G Γ is defined as the quotient ( * u∈V G u )/ [G v , G w ] for {v, w} ∈ E . Kramer and the third author proved in [KV19] that if the vertex set of Γ is not equal to S ∪ {w ∈ V | {v, w} ∈ E for all v ∈ S} where the subgraph generated by S is complete, then Epi(LCG, G Γ ) = cEpi(LCG, G Γ ). Further, the second and third author proved in [MV20] that if G is a subgroup of a CAT(0) group whose torsion subgroups are finite and G does not have non-trivial finite normal subgroups, then Epi(LCG, G) = cEpi(LCG, G) by geometric means.…”
Section: Introductionmentioning
confidence: 99%
“…Free (abelian) groups were classically shown to be cm-slender, lcH-slender and n-slender (see [23] and [34]). More recent work has shown that torsion-free word hyperbolic groups, right-angled Artin groups, braid groups and many other groups satisfy various of these slenderness conditions (see [17,20,39,44]). Note that a group which is either n-slender, cm-slender, or lccH-slender must be torsion-free.…”
Section: Problem 1 Does There Exist a Finitely Generated (Countable) Torsion-free Acylindrically Hyperbolic Group Which Does Not Admit Unmentioning
confidence: 99%
“…Another important result in this direction is a theorem of Nikolov and Segal [45, Theorem 1.1], which says that every abstract homomorphism from a finitely generated in topological sense profinite group to any profinite group is continuous. Papers [14,17,20,23,39,43,49] deal with automatic continuity of abstract homomorphisms from locally compact Hausdorff groups to some discrete groups; papers [17,20] also deal with completely metrizable groups as domains.…”
Section: Introductionmentioning
confidence: 99%
“…Our focus here is on continuity of group homomorphisms from locally compact Hausdorff groups into Artin groups. Many types of Artin groups are known to be lcH-slender such as right-angled Artin groups [KV19], [CK20], [MV20], Artin groups of spherical type [KV19] and more generally Artin groups of FC-type [KMV21]. We conjecture:…”
Section: Introductionmentioning
confidence: 99%